2020
DOI: 10.1177/1024907920934901
|View full text |Cite
|
Sign up to set email alerts
|

A review on iatrogenic botulism

Abstract: Background: With the flourishing application of botulinum toxin cosmetically and therapeutically is the emergence of iatrogenic botulism, a new type of botulism in addition to the traditional ones. Objectives: We aim at a comprehensive review of the clinical characteristics of iatrogenic botulism. Methods: The available publications are retrieved and studied. Results: Botulinum toxin blocks cholinergic transmission in the neuromuscular junctions and autonomic ganglia. The blockade can spread from the site of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 71 publications
(228 reference statements)
0
11
0
Order By: Relevance
“…3,7 It binds to free circulating toxin but cannot reverse the settled neurotoxicity. 4 Antitoxin induces recovery not only by binding of the free intravascular botulinum toxin but also by increasing acetylcholine release in neuromuscular junction. Antitoxin also may provide the redistribution of botulinum toxin from the receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7 It binds to free circulating toxin but cannot reverse the settled neurotoxicity. 4 Antitoxin induces recovery not only by binding of the free intravascular botulinum toxin but also by increasing acetylcholine release in neuromuscular junction. Antitoxin also may provide the redistribution of botulinum toxin from the receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Antitoxin administration is considered effective when it is applied in the first 48 hours of the exposure 3,7 . It binds to free circulating toxin but cannot reverse the settled neurotoxicity 4 . Antitoxin induces recovery not only by binding of the free intravascular botulinum toxin but also by increasing acetylcholine release in neuromuscular junction.…”
Section: Discussionmentioning
confidence: 99%
“…All serotypes are neurotoxins, except for C2. Human botulism is known to be caused by serotypes A, B, E, and rarely F, while botulism in fish, birds, and non-human mammals is mainly caused by serotypes C1 and D [ 22 ]. Botulinum neurotoxin serotype A (BoNTA) is the most toxic substance known to man with an estimated intravenous lethal dose (LD50) of 1–2 nanogram per kilogram (ng/kg) in humans [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization medical product alert from August 2022 had reported 5 falsified batches of a BoNT product detected in 5 countries, namely, Jordan and Turkey in May 2022, Kuwait and the United Kingdom in June 2022, and Poland in July 2022 3 . Studies have revealed that iatrogenic botulism can be due to increased frequency in dosage for therapeutic use, which needs close monitoring of unlicensed BoNT A product, and adverse effects are more for cosmetic use than for therapeutic use 4,5 . Recently, the public interest is more inclined toward its off-label cosmetics use, which leads to its erroneous use such as obesity treatment as in the case of the recent outbreak.…”
mentioning
confidence: 99%
“…3 Studies have revealed that iatrogenic botulism can be due to increased frequency in dosage for therapeutic use, which needs close monitoring of unlicensed BoNT A product, and adverse effects are more for cosmetic use than for therapeutic use. 4,5 Recently, the public interest is more inclined toward its off-label cosmetics use, which leads to its erroneous use such as obesity treatment as in the case of the recent outbreak. These studies highlight that BoNT product either as unlicensed form or off-label indications leads to life threatening adverse effects, which needs to be strictly regulated at all levels for the appropriate use.…”
mentioning
confidence: 99%